Metabolic and Physiological Impact of Probiotics or Direct-Fed-Microbials on Poultry: A Brief Review of Current Knowledge - Chichlowski, M.; Croom, J.; McBride, B.W.; Havenstein, G.B.; Koci, M.D. (International Journal of Poultry Science, 2007)
The poultry industry is facing a ban on the use of antibiotic feed additives in many parts of the world. Consequently, there is a growing interest in finding viable alternatives for disease prevention and growth enhancing supplements. The effects of probiotics or direct fed microbials (DFM) on gut health and performance in poultry as well as other species are presented. The interactions between intestinal microbiota, the gut epithelium and the immune system are important in the competitive exclusion process. The mechanisms by which probiotics operate include spatial exclusion, micro-environmental alterations, production of antimicrobial substances and epithelial barrier integrity. The preponderance of research data in this field suggests the likelihood of a small but additive series of beneficial changes from an animal`s exposure to probiotics. Further investigations will be needed to fully characterize the effects and sustained outcomes of probiotic and DFM treatments in poultry.